Effect of fluoroscopic X‐ray beam spectrum on air‐kerma measurement accuracy: implications for establishing correction coefficients on interventional fluoroscopes with KAP meters - Wunderle, Kevin A. (J Appl Clin Med Phys, 2016)
The first goal of this study was to investigate the accuracy of the displayed reference plane air kerma ([Formula: see text]) or air kerma‐area product ([Formula: see text]) over a broad spectrum of X‐ray beam qualities on clinically used interventional fluoroscopes incorporating air kerma‐area product meters (KAP meters) to measure X‐ray output. The second goal was to investigate the accuracy of a correction coefficient (CC) determined at a single beam quality and applied to the measured [Formula: see text] over a broad spectrum of beam qualities. Eleven state‐of‐the‐art interventional fluoroscopes were evaluated, consisting of eight Siemens Artis zee and Artis Q systems and three Philips Allura FD systems. A separate calibrated 60 cc ionization chamber (external chamber) was used to determine the accuracy of the KAP meter over a broad range of clinically used beam qualities. For typical adult beam qualities, applying a single CC determined at 100 kVp with copper (Cu) in the beam resulted in a deviation of [Formula: see text] due to beam quality variation. This result indicates that applying a CC determined using The American Association of Physicists in Medicine Task Group 190 protocol or a similar protocol provides very good accuracy as compared to the allowed [Formula: see text] deviation of the KAP meter in this limited beam quality range. For interventional fluoroscopes dedicated to or routinely used to perform pediatric interventions, using a CC established with a low kVp ([Formula: see text]) and large amount of Cu filtration ([Formula: see text]) may result in greater accuracy as compared to using the 100 kVp values. KAP meter responses indicate that fluoroscope vendors are likely normalizing or otherwise influencing the KAP meter output data. Although this may provide improved accuracy in some instances, there is the potential for large discrete errors to occur, and these errors may be difficult to identify. PACS number(s): 87.59.C‐, 87.59.cf, 87.53.Bn